2008
DOI: 10.1021/nn800395t
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of In Vivo Anticancer Effects of Cisplatin by Incorporation Inside Single-Wall Carbon Nanohorns

Abstract: Cisplatin (CDDP) was incorporated inside single-wall carbon nanohorns with holes opened (SWNHox) by a nanoprecipitation method that involved dispersion of CDDP and SWNHox in a solvent followed by the solvent evaporation. The incorporated CDDP quantity increased from the previously reported value of 15 to 46%, and the total released quantity of CDDP also increased from 60 to 100% by changing the solvent from dimethylformamide to water. Concurrently, in vitro anticancer efficiency of CDDP@SWNHox increased to 4-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
151
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(153 citation statements)
references
References 25 publications
1
151
1
Order By: Relevance
“…[1][2][3][4] So far, reports on the SWCNHs have focused on drug release in vitro, tumor-targeting therapy, or thermal treatment after intramuscular injection or tail vein injection in vivo. 7 The previous studies on the interaction between SWCNHs and cells have mostly emphasized on cellular uptake and intracellular trafficking, but seldom on epithelial cells, although epithelial cell membranes as the typical biological barrier constitute the prime obstacle for the transport of therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] So far, reports on the SWCNHs have focused on drug release in vitro, tumor-targeting therapy, or thermal treatment after intramuscular injection or tail vein injection in vivo. 7 The previous studies on the interaction between SWCNHs and cells have mostly emphasized on cellular uptake and intracellular trafficking, but seldom on epithelial cells, although epithelial cell membranes as the typical biological barrier constitute the prime obstacle for the transport of therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…They are novel nanostructure carbon materials generating much enthusiasm in biomedical applications, such as drug delivery, photo-hyperthermia (due to their intrinsic therapeutic effects), and magnetic resonance analysis, due to their several advantages over other carbon materials such as single-walled carbon nanotubes. [1][2][3][4][5][6][7][8][9][10][11][12] Besides their high purity, uniform size, and absence of metal catalysts, they have an extremely large specific surface area. 8 Furthermore, their surface area can be enlarged, holes can be opened, and oxygen functional groups can be introduced by oxidation at their …”
Section: Introductionmentioning
confidence: 99%
“…Although carbon nanotubes are completely insoluble in all solvents, creating toxicity problems, limiting their length and diameter diminish this toxicity, and chemical modifications to their structure transform them in water-soluble carriers, increasing their biocompatibility and decreasing their toxicity [292][293][294]. Different anticancer drugs can be included in their inner cavity [295,296] or in their surface [297] with a high payload due to their ultrahigh surface area. These novel carriers have the ability of cross the plasma membrane and enter into the cancerous cells (by endocytosis or penetration like a needle), having no influence the type of functionalization of the nanotubes or the type of cancer cells [298,299].…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…7 Fan et al 8 showed that no obvious decrease of cell viability was observed for Hela cells incubated with gum arabic modified SWNHs (10-1000 µg/mL). This result suggested that the nanoparticles were nontoxic to Hela cells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their large surface area, their particular surface structures, and especially their affinity for biomolecules, SWNHs may offer biomedical and pharmaceutical potential. [2][3][4][5][6][7][8] Some researchers 4 applied oxidized SWNHs (SWNHox) as carriers of the anticancer drug cisplatin and found that cisplatin released slowly from the SWNHs into aqueous solution and effectively inhibited the growth of human lung cancer NCI-H460 cells. They also found that as a carrier material, SWNHox itself did not promote or suppress the growth of lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%